UTILIZING SNAKES AND LADDERS MEDIA IN LEARNING MATHEMATIC ELEMENTARY SCHOOL STUDENTS - Ukhti Hanifah Tiarawati; Sukartono (Jurnal Cakrawala Pendas, 2024)
This research is motivated by the selection of learning methods that are not appropriate, resulting in a lack of interest in learning in students, especially in mathematics. The fact found in the field is that teachers in learning activities only use the lecture method, this causes the learning to feel very monotonous so that students feel bored and lack interest in learning. The purpose of this study was to describe the use of snakes and ladders media in learning math with length, weight, and time material in standard units in grade 2 in elementary school.  This research uses a qualitative approach with a case study design. This research data consists of primary data and secondary data. Data collection used interview, observation, and documentation techniques. Data validity used source triangulation and technique triangulation. Data analysis used the Miles and Huberman model which consists of data collection, data reduction, data presentation, and conclusion drawing. Based on the results of the study, it can be concluded that the use of snakes and ladders media in learning mathematics material on length, weight, and time in standard units can foster students' interest in learning. The selection of media in the form of a snakes and ladders game can foster students' interest in learning which is indicated by the interest, enthusiasm, and enthusiasm of students in playing the media and involving the active role of students so that learning is fun.